2013
DOI: 10.1097/cej.0b013e328355ed23
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics enhance the clearance of human papillomavirus-related cervical lesions

Abstract: Probiotics have been proposed for a number of urogenital infectious conditions. In this study, we examine a possible effect on human papillomavirus (HPV)-related precancerous lesions in cervical cytology. We conducted a prospective controlled pilot study, in which 54 women with an HPV+low-grade squamous intraepithelial lesion diagnosis in their PAP smear were followed for 6 months. The intervention group consumed a daily probiotic drink during the study period; the control group received no treatment, accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 0 publications
0
75
0
1
Order By: Relevance
“…After 6 months, the probiotic users had double the chance of clearance of cytological abnormalities (60% vs. 31% in women who received no treatment, p = 0.05). Additionally, HPV was cleared in 29% of probiotic users and only 19% of control patients, although not significant (p = 0.41) [80]. These results suggest that probiotics may play a role in promoting the clearance of HPV, although the mechanism is unknown.…”
Section: Referencesmentioning
confidence: 89%
See 2 more Smart Citations
“…After 6 months, the probiotic users had double the chance of clearance of cytological abnormalities (60% vs. 31% in women who received no treatment, p = 0.05). Additionally, HPV was cleared in 29% of probiotic users and only 19% of control patients, although not significant (p = 0.41) [80]. These results suggest that probiotics may play a role in promoting the clearance of HPV, although the mechanism is unknown.…”
Section: Referencesmentioning
confidence: 89%
“…However, it is important to note that the effects of bacteria on cultured cells may not accurately approximate the effects of probiotics on cells in vivo, therefore more research is needed in this area. In the third study, 54 women with HPV + low-grade squamous intraepithelial lesions were monitored for 6 months; the intervention group consumed a daily probiotic drink containing Lactobacillus casei, while the control group received no treatment [80]. After 6 months, the probiotic users had double the chance of clearance of cytological abnormalities (60% vs. 31% in women who received no treatment, p = 0.05).…”
Section: Referencesmentioning
confidence: 97%
See 1 more Smart Citation
“…A study involving 54 women reported that daily probiotic consumption for 6 months enhanced the clearance of human papillomavirus, which is known to cause cervical cancer [54]. In animal models, oral probiotic administration protects against Salmonella typhimurium infection by activating the phagocytic and microbicidal activity of peritoneal and spleen macrophages [55].…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 99%
“…A pilot study suggested that probiotic promotes the clearance of HPV-related cytological abnormalities [95] . Common vaginal lactobacilli exerted cytotoxic effects on cervical tumour cells independently of pH and lactate [96] .…”
Section: Nutrtion and Breast Cancermentioning
confidence: 99%